2007
DOI: 10.1073/pnas.0611618104
|View full text |Cite
|
Sign up to set email alerts
|

CD8 tumor-infiltrating lymphocytes are predictive of survival in muscle-invasive urothelial carcinoma

Abstract: with UC showed that patients with advanced UC (pT2, pT3, or pT4) and higher numbers of CD8 TILs within the tumor (>8) had better disease-free survival (P < 0.001) and overall survival (P ‫؍‬ 0.018) than did patients with similar-staged UC and fewer intratumoral CD8 TILs. We conclude that the extent of intratumoral CD8 TILs is an important prognostic indicator in advanced UC.CD8 T cell ͉ major histocompatibility complex ͉ cancer testis antigen ͉ NY-ESO-1 ͉ bladder

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
322
7
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(351 citation statements)
references
References 22 publications
19
322
7
3
Order By: Relevance
“…A high number of tumor-infiltrating CD8 1 T lymphocytes were observed as a favorable prognostic factor for survival in some studies of human cancers, including endometrial cancer, 32 ovarian cancer, 8 colorectal cancer, 33 esophageal cancer 34 and urothelial carcinoma. 35 Other studies on non-small cell lung cancer, 36 anal squamous cell carcinoma 24 and renal cell carcinoma 37 reported that CD8 1 T lymphocytes were a negative prognostic factor. The CD8 1 T-cell subpopulation has been considered to be the effector in the antitumor response; however, when the status of activation was explored, most of the cells were underprimed (CD45RO 1 ) 38 or inactivated (in this study, the GrB/CD8 ratio was 7/48), regardless of the effector/target ratio within the tumor tissue (data not shown).…”
Section: Comparative Numbers Of Cd4mentioning
confidence: 98%
“…A high number of tumor-infiltrating CD8 1 T lymphocytes were observed as a favorable prognostic factor for survival in some studies of human cancers, including endometrial cancer, 32 ovarian cancer, 8 colorectal cancer, 33 esophageal cancer 34 and urothelial carcinoma. 35 Other studies on non-small cell lung cancer, 36 anal squamous cell carcinoma 24 and renal cell carcinoma 37 reported that CD8 1 T lymphocytes were a negative prognostic factor. The CD8 1 T-cell subpopulation has been considered to be the effector in the antitumor response; however, when the status of activation was explored, most of the cells were underprimed (CD45RO 1 ) 38 or inactivated (in this study, the GrB/CD8 ratio was 7/48), regardless of the effector/target ratio within the tumor tissue (data not shown).…”
Section: Comparative Numbers Of Cd4mentioning
confidence: 98%
“…The presence of CD8 + TIL is associated with improved survival in patients with muscle invasive urothelial carcinoma while the frequency of immunosuppressive regulatory T cells and macrophages correlates with reduced survival. 9 Tumors characterized by high CD4 + T cells, low regulatory T cells, and low CD68 + or CD163 + macrophages are associated with prolonged recurrence free survival in patients that responded to BCG therapy. 10 Thus, while the profile of anti-tumor and pro-tumor immune subsets in bladder cancer are predictive of clinical outcomes, the presence of TIL alone is not associated with the suppression of tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Results from numerous studies on diverse human cancers have suggested that the infiltration of tumor-reactive T cells, especially CD8 þ T cells, strongly correlates with tumor regression and better prognosis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, endogenous tumor-reactive T cells are usually present in low numbers and often become anergic, likely due to the immunosuppressive environment in the tumor sites.…”
Section: Introductionmentioning
confidence: 99%